2014
DOI: 10.1111/nyas.12467
|View full text |Cite
|
Sign up to set email alerts
|

Case studies continue to illuminate the cognitive neuroscience of memory

Abstract: The current ubiquity of functional neuroimaging studies, and the importance they have had in elucidating brain function, obscures the fact that much of what we know about brain-behavior relationships derives largely from the study of single- and multiple-patient cases. A major goal of the present review is to describe how single cases continue to uniquely and critically contribute to cognitive neuroscience theory. With several recent examples from the literature, we demonstrate that single cases can both chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 229 publications
(418 reference statements)
1
39
0
Order By: Relevance
“…The current results lend validity to cross-species studies and less direct methods of investigating dentate gyrus contributions to pattern separation in humans, including computational models and high-resolution fMRI (Berron et al, 2016;Rosenbaum, Gilboa, & Moscovitch, 2014).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The current results lend validity to cross-species studies and less direct methods of investigating dentate gyrus contributions to pattern separation in humans, including computational models and high-resolution fMRI (Berron et al, 2016;Rosenbaum, Gilboa, & Moscovitch, 2014).…”
Section: Discussionsupporting
confidence: 60%
“…Although single case studies of individuals with hippocampal damage have been invaluable in defining the neural architecture of the medial temporal lobes and in confirming hypotheses about hippocampal involvement in episodic and semantic memory (Rosenbaum et al, 2014), they have inherent limitations. In some cases, group designs may be superior at assembling converging human and animal evidence in testing complex predictions of basic cognitive processing systems (Robertson, Knight, Rafal, & Shimamura 1993).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…The MTL has long been understood to be critical for episodic memory, based on decades of research that was spurred by the landmark case of Henry Molaison (HM), whose ability to remember new experiences from his daily life was dramatically impaired following bilateral resection of the hippocampus, and portions of the neighboring MTL cortical structures ( perirhinal, parahippocampal, and entorhinal cortex) (Scoville and Milner 1957;Corkin 2013;Squire and Dede 2015). Although studies of HM and other patients suffering MTL lesions have yielded a multitude of novel insights about the role of the MTL in declarative memory (Eichenbaum and Cohen 2001;Squire et al 2004;Moscovitch et al 2006;Squire and Bayley 2007;Graham et al 2010;Greenberg and Verfaellie 2010;Montaldi and Mayes 2010;Rosenbaum et al 2014), a challenge for neuropsychological studies is to identify whether the observed memory deficits reflect impairments at encoding, retrieval, or both. Noninvasive human imaging techniques complement lesion studies, as they provide a critical set of tools for studying healthy brain function by measuring neural re-sponses at the time memories are encoded and, as we will later discuss, at the time that they are retrieved.…”
Section: Imaging and The Subsequent Memory Paradigmmentioning
confidence: 99%
“…A system's constituents-normally masked by the fluid manner in which they work together to affect a common end-are laid bare as the whole of which they are part unravels (e.g., Klein, Rozendal, & Cosmides, 2002;Rosenbaum, Gilboa, & Moscovitch, 2014). Accordingly, in what follows I draw on evidence from individuals suffering impairments of episodic memory and autonoetic consciousness.…”
Section: Data From Patients Suffering Episodic Memory Impairmentmentioning
confidence: 99%